THE EFFECTIVENESS OF COLLABORATIVE MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION IN 3T (UNDERDEVELOPED, FRONTIER, AND OUTERMOST) REGIONS - Mohamad Kamil Salas; Masluhah; Mahrus (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the effectiveness of collaborative management in improving the quality of education in 3T (Disadvantaged, Frontier, and Outermost) areas. 3T areas face various challenges such as limited infrastructure, minimal human resources, and limited access to education. Through a collaborative management approach involving the government, educational institutions, the community, and the private sector, this study found that collaboration between stakeholders can create synergy in the planning, implementation, and evaluation of education programs. The results of the study indicate that a collaborative approach can improve access, quality, and relevance of education in 3T areas, especially through optimizing resources, improving teacher competency, and active community participation. However, the success of implementing collaborative management is largely determined by commitment, effective communication, and ongoing policy support. Therefore, systematic efforts are needed to strengthen institutions and create a collaborative environment that supports improving the quality of education evenly in 3T areas.